Communication about clinical trials as observed and experienced: the views of parents and practitioners. (29th September 2015) - Shilling, V; Hickey, H; Smyth, R; Sowden, E; Williamson, P; Young, B
Abstract : Aims: To observe the process of communication about trials and compare these observations with parents' and practitioners' experiences of the process. Methods: Qualitative observational and interview study conducted alongside three trials of medicines for children. Data were verbatim transcripts of (1) 33 family-practitioner trial discussions, and qualitative interviews about the experience of the trial communication with (2) the 33 corresponding families and (3) 19 paediatric practitioners who recruit children to trials. 30/33 families had consented to one of the trials, one had withdrawn. Analysis followed the principles of the constant comparative method. Results: Parents' interaction with practitioners during the observed trial discussions varied but was generally low. They contributed a mean of only 18% of the total utterances and asked few questions, with 11 families asking only one question and eight asking none at all. Regardless of their observed level of interactivity, when interviewed, parents spoke of their sense of comfort during the discussion, their confidence in the practitioner and the trial, and their belief that their child's health was the practitioner's overriding concern. Parents were also satisfied with the amount of information they had received. By contrast, many practitioners were concerned about the amount of information they had to provide and believed this overwhelmed families. They spoke of the tension between providing "sufficient" information and being flexible enough to meet with individual families' needs. Some practitioners disliked approaching families about trials and constructed research as a burden for families. Parents did not speak of trials as a burden; rather, they regarded trials positively as offering potential benefit and hope. Parents and practitioners agreed that the trial information leaflets were too long and that the face-to-face discussions were more important. Ho-wever, while some practitioners thought the leaflets served regulatory and ethical requirements and regarded them of little use to families, parents reported that they used and valued the leaflets. Conclusion: Parents were far more accepting of the need for research and positive about how communication about trials was conducted than practitioners anticipated; however, both parties agreed that trial information leaflets should be shorter. Implications for practitioner training will be considered.